Measurement of Lead Localization Accuracy Based on Magnetic Resonance Imaging - He, Changgeng; Zhang, Feng; Li, Linze; Jiang, Changqing; Li, Luming (Frontiers in Neuroscience, 2021)
Post-implantation localization of deep brain stimulation (DBS) lead based on a magnetic resonance (MR) image is widely used. Existing localization methods use artifact center method or template registration method, which may lead to a considerable deviation of >2 mm, and result in severe side effects or even surgical failure. Accurate measurement of lead position can instantly inform surgeons of the imprecise implantation. This study aimed to identify the influencing factors in DBS lead post-implantation localization approach, analyze their influence, and describe a localization approach that uses individual template method to reduce the deviation.